(untitled) (American International Journal of Education and Linguistics Research, 2023)
Code-switching is a natural phenomenon that allows educators and learners alike to communicate in a classroom setting, which is multilingual in nature with diverse linguistic backgrounds. Hence, this study has aimed to explore whether higher education academics in English language teaching classrooms incorporate code-switching or not and what are the reasons for their incorporation. To achieve the aims of this study, two research tools were used for data collection namely checklist and observation. The checklist consisted of eleven reasons that are introduced by Gulzar (2010) for code-switching that showed where higher education academics code-switch in their classrooms and in which contexts. On the other hand, lesson observations were made during the participant’s classroom teaching and notes were taken. It is envisaged that the aim of code-switching is mainly to transfer the understanding of materials being used in ELT classrooms in the most effective manner. More imperatively, a mixed method research design was used to achieve the results output of the present study. The study has found that code-switching is indeed a spontaneous occurrence that happens naturally, and higher education academic professionals use it as a linguistic tool to assist learners in comprehending difficult nuances. Code-switching worked as a bridge between higher education academics and learners alike. JEL Classification Codes: L33, H44, J24.